1999
DOI: 10.1046/j.1365-2788.1999.043005372.x
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison, self‐esteem and depression in people with intellectual disability

Abstract: The present study explores the relationship between social comparison processes, self-esteem and depression in people with intellectual disability. Forty-three people with mild and moderate intellectual disability completed adapted measures of self-esteem and social comparison. The social comparison scale offers subscale scores on achievement, social attractiveness and group belonging dimensions. The self-esteem scale offers subscale scores for positive and negative self-esteem. A significant positive correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 18 publications
1
175
1
4
Order By: Relevance
“…One possible explanation is that the more intensive input may have led participants to make negative self-comparisons with mothers in the general population. Such social comparisons have been found to be associated with poor self-esteem (Dagnan and Sandhu, 1999) and the mothers in the present study certainly portrayed the additional input as disempowering, undermining of their sense of self-esteem and their role as mothers. This may also partly offer an explanation for why mothers appeared to prefer to turn to unhelpful informal supports for the care of their infant, in preference to seeking more intensive involvement from professionals.…”
Section: Discussionmentioning
confidence: 48%
“…One possible explanation is that the more intensive input may have led participants to make negative self-comparisons with mothers in the general population. Such social comparisons have been found to be associated with poor self-esteem (Dagnan and Sandhu, 1999) and the mothers in the present study certainly portrayed the additional input as disempowering, undermining of their sense of self-esteem and their role as mothers. This may also partly offer an explanation for why mothers appeared to prefer to turn to unhelpful informal supports for the care of their infant, in preference to seeking more intensive involvement from professionals.…”
Section: Discussionmentioning
confidence: 48%
“…Dagnan and Sandhu (1999) investigated the relationship between social comparison, depression and self-esteem in individuals with disabilities. They found that total social comparison scores positively associated with total self-esteem scores and negatively associated with reported levels of depression (Dagnan and Sandhu 1999).…”
Section: Self-esteemmentioning
confidence: 99%
“…Dagnan and Sandhu (1999) investigated the relationship between social comparison, depression and self-esteem in individuals with disabilities. They found that total social comparison scores positively associated with total self-esteem scores and negatively associated with reported levels of depression (Dagnan and Sandhu 1999). Literature beyond the Dagnan and Sandhu study focused on self-esteem for those with physical disabilities (see Jemtå et al 2009;Manuel et al 2003;Miyahara and Piek 2006).…”
Section: Self-esteemmentioning
confidence: 99%
“…84 Scores of ≥ 13 on the Glasgow scales are indicative of clinical levels of depression or anxiety. Self-reported quality of life was assessed using the ComQoL-ID; 77 the scaling exercises that were administered at the baseline assessment (see Baseline measures, above) were omitted from follow-up assessments.…”
Section: Follow-up Assessmentsmentioning
confidence: 99%